Effectiveness of Telemonitoring for Reducing Exacerbation Occurrence in COPD Patients With Past Exacerbation History: A Systematic Review and Meta-Analysis - Lu, Jing-wen; Wang, Yu; Sun, Yue; Zhang, Qin; Yan, Li-ming; Wang, Ying-xi; Gao, Jing-han; Yin, Yan; Wang, Qiu-yue; Li, Xue-lian; Hou, Gang (Frontiers in Medicine, 2021)
Background: Although an increasing number of studies have reported that telemonitoring (TM) in patients with chronic obstructive pulmonary disease (COPD) can be useful and efficacious for hospitalizations and quality of life, its actual utility in detecting and managing acute exacerbation of COPD (AECOPD) is less established. This meta-analysis aimed to identify the best available evidence on the effectiveness of TM targeting the early and optimized management of AECOPD in patients with a history of past AECOPD compared with a control group without TM intervention. Methods: We systematically searched PubMed, Embase, and the Cochrane Library for randomized controlled trials published from 1990 to May 2020. Primary endpoints included emergency room visits and exacerbation-related readmissions. P-values, risk ratios, odds ratios and mean differences with 95% confidence intervals were calculated. Results: Of 505 identified citations, 17 original articles with both TM intervention and a control group were selected for the final analysis (N=3,001 participants). TM was found to reduce emergency room visits [mean difference (MD) -0.70, 95% confidence interval (CI) -1.36 to -0.03], exacerbation-related readmissions [risk ratio 0.74, 95% CI 0.60 to 0.92], exacerbation-related hospital days (MD -0.60, 95% CI -1.06 to -0.13), mortality (odds ratio 0.71, 95% CI 0.54 to 0.93) and the SGRQ score (MD -3.72, 95% CI -7.18 to -0.26) but did not make a difference with respect to all-cause readmissions, the rate of exacerbation-related readmissions, all-cause hospital days, time to first hospital readmission, anxiety and depression, and exercise capacity. Furthermore, the subgroup analysis by observation period showed that longer TM (≥12 months) was more effective in reducing readmissions. Conclusions: TM can reduce emergency room visits and exacerbation-related readmissions, as well as AE-related hospital days, mortality and the SGRQ score. The implementation of TM intervention is thus a potential protective therapeutic strategy that could facilitate the long-term management of AECOPD. Register of systematic review This systematic review and meta-analysis is reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Statement and was registered at International Prospective Register of Systematic Reviews (number: CRD42020181459).